Effect of perfusion pressure sensors on posterior capsule elevation in the porcine eye model with eyelid speculums - Hisaharu Suzuki (Scientific Reports)
Abstract This study evaluated the posterior capsule elevation ratio after occlusion break in a porcine eye model with an eyelid speculum (ES) using Centurion Vision System with Active Sentry handpiece (AS). The mean intraocular pressure of the porcine eyes with the ES was significantly higher than that of without the ES (15.42 ± 4.10 mmHg vs. 21.86 ± 4.12 mmHg, P = 0.0003). Changes in the posterior capsule elevation were observed using the slit side view method in the following four groups: with an ES using AS [AS (ES+)], without an ES using AS [AS (ES−)], with an ES using the Ozil handpiece [OZ (ES+)], and without an ES using OZ [OZ (ES−)]. Eleven eyes in each group were tested. AS (ES+) and OZ (ES+) had a significantly higher rate of posterior capsule elevation than did AS (ES−) and OZ (ES−) (P = 0.0135 and P = 0.010). AS (ES+) and AS (ES−) significantly suppressed posterior capsule elevation compared with OZ (ES+) and OZ (ES−) (P = 0.034 and P = 0.045). Porcine eyes with ES had increased IOP and greater posterior capsule elevation after occlusion break than did those without. AS effectively suppressed posterior capsule elevation better than did OZ.